Productivity evaluation of multi-stage fracturing horizontal wells in shale gas reservoir with complex artificial fracture occurrence - HU Zhijian, LI Shuxin, WANG Jianjun, ZHOU Hong, ZHAO Yulong, ZHANG Liehui (Youqicang pingjia yu kaifa)
Considering complex shape and non-uniform distribution of fracturing fractures in shale reservoir, on the basis of multiple migration mechanisms a unified apparent permeability model is developed, incorporating two types of pore apparent permeability based on multiple migration mechanisms. This model serves as the foundation for establishing a gas reservoir-fracture-wellbore coupled seepage model, utilizing real space source function theory and pressure drawdown superposition principle. Through simulations and analyses, the study investigates the effects of micro seepage, fracture shape and non-uniform distribution of fractures on shale gas productivity. The demonstrate that micro seepage significantly impacts shale gas well production, with daily gas production being 20.3 % higher when considering micro seepage during the initial stage compared to neglecting it. Furthermore, the productivity of wells with complex fractures is lower than that of wells with ideal rectangular fractures, and star-shaped fractures exhibit the lowest productivity. The non-uniform distribution of fractures also affects the productivity of horizontal wells, and an optimal fracture layout is identified. The model takes into account both the micro seepage mechanism and actual fracturing fracture of shale gas, providing valuable guidance for the productivity research of fractured horizontal wells in shale gas reservoir.